Odpowiedzi

2010-03-19T14:44:34+01:00
{3x-y=-5=>y=-5-3x
{5x-y=7
5x-(-5-3x)=-7
5x+5+3x=-7
8x=-12
x=-12/8=-3/2
y=-5-3*(-3/2)=-5-9/2=-5-4,5=-9,5

{x+3y=-7=>x=-7-3y
{2y-x=-8
2y-(-7-3y)=-8
2y+7+3y=-8
5y=-15
y=-3
x=-7-3*(-3)=-7+6=-1

{5x-y=21
{y-2x=-3=>y=-3+2x
5x+3-2x=21
3x=18
x=6
y=-3+2*6=-3+12=9

{3x+y=10=> y=10-3x
{2x-y=15
2x-10+3x=15
5x=25
x=5
y=10-3*5=10-15=-5

{x+4y=37=> x=37-4y
{2x+5y=53
2(37-4y)+5y=53
74-8y+5y=53
3y=-21
y=-7
x=37-4*(-7)=34-28=6
2010-03-19T14:52:34+01:00
A)
{3x-y=-5
{5x-y=7

-y=-5-3x
5x-y=7

y=5+3x
5x-5+3x=7
8x=12
x=1,5

y=5+3*1,5
y=5+4,5
y=9,5


b)
{x+3y=-7
{2y-x=-8

x=-7-3y
2y+7-3y=-8
-y=-15
y=15

x=-7-3*15
x=-7-45
x=-52


c)
{5x-y=21
{y-2x=-3

5x-y=21
y=-3+2x

5x+3+2x=21
7x=24
x=3⅛

y=-3+2*3⅛
y=-3+6,25
y=3,25


d)
{3x+y=10
{2x-y=15

y=10-3x
2x-10-3x=15
-x=25
x=25

y=10-3*25
y=10-75
y=-65


e)
{x+4y=37
{2x+5y=53

x=37-4y
2(37-4y)+5y=53
74-8y+5y=53
-3y=-21
y=7

x=37-4*7
x=37-28
x=9